Analysis of the Deformation of Traditional Multi-Storey Residential Buildings Caused by The Curvature of the Terrain – Case of Study - Kapusta, Łukasz; Szojda, Leszek (Archives of Mining Sciences, 2025)
Knowledge of the relationship between the curvature of the terrain and the curvature of the building can be a significant factor in assisting the process of introducing building prophylaxis for existing residential buildings made of traditional technology. Every year, a significant proportion of the costs resulting from the mining damage is spent on repairs to such buildings. In this study, the relationship between the curvature of the terrain and the curvature of two four-storey traditional residential buildings was determined. To this purpose, surveying was carried out for the two selected buildings and the terrain area near the buildings. This allowed us to describe the relationship between the two curvatures. Subsequently, FEM analyses were carried out in the building-substrate system for both buildings. The relationship between the curvatures was determined by the coefficient α and displayed graphically. The determined relationship may in future be a tool to assist in the design process of building prevention solutions for similar existing structures. It must be noted though, that the analyses were limited to a single experiment. More data should be collected from other research facilities to permanently introduce similar simplification solutions into design practice.
Keywords: Mining subsidence; ground curvature; geodesy monitoring; numerical analysis; masonry structures